PENGARUH PELATIHAN DAN LINGKUNGAN KERJATERHADAP KINERJA PEGAWAI BPBD DKI JAKARTA - Hotman Napitupulu; Tini Juartini (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
The aim of this research is to analyze the influence of training and work environment on the performance of BPBD DKI Jakarta employees. This research uses quantitative methods. The analysis technique uses multiple and simple linear regression. The research results found that: (1) Training has a positive and significant effect on the performance of BPBD DKI Jakarta employees, (2) The work environment has a positive and significant effect on the performance of BPBD DKI Jakarta employees, (3) Training and the work environment have a positive and significant effect on employee performance BPBD DKI Jakarta.